(untitled) (NURVERSE : Journal of Islamic Studies & Applied Science Integration, 2026)
Money politics has long been a chronic disease within Indonesian elections. It takes various forms, ranging from the blatant cash handouts known as "dawn attacks" to social assistance deliberately distributed close to campaign season. By drawing on a range of existing studies, this paper attempts to examine the extent to which this practice shapes people’s decisions at the ballot box, as well as its impact on the quality of democracy, supplemented with the latest data following the 2024 simultaneous elections. Muhtadi’s (2020) findings reveal a rather concerning picture, around 19.4 to 33.1 percent of voters in the 2019 election had received money or rewards from candidates, placing Indonesia third highest in the world for similar cases. According to Aspinall and Berenschot (2019), this is no longer an occasional violation but has become deeply ingrained in the way Indonesian politics operates. It is hardly surprising, then, that Indonesia’s democracy score has also declined for three consecutive years, falling from 6.71 in 2022 to 6.44 in 2024, with political culture and civil liberties standing out as the weakest aspects. This has led people to vote based on what they personally gain rather than the policy platforms on offer, leaving elected officials with little concern for accountability.